Wojewódzki Urząd Kontroli Prasy, Publikacji i Widowisk w okresie nacjonalizacji rynku książki w Poznaniu (1946–1955) - Nowak, Piotr (Biblioteka Uniwersytecka w Poznaniu, 2011)
Po przedstawieniu struktury i zasad funkcjonowania Wojewódzkiego Urzędu Kontroli Prasy, Publikacji i Widowisk (WUKPPiW) w Poznaniu autor artykułu opisuje rolę tej placówki w procesie likwidacji spółdzielczych oraz prywatnych wydawnictw poznańskich. Udowadnia, że przez istnienie stalinowskiej cenzury prewencyjnej ówczesnym władzom udało się przyspieszyć nacjonalizację wspomnianych sektorów wydawniczych. W artykule wykorzystano bardzo obszerny zespół archiwalny pozostały po WUKPPiW w Poznaniu, przechowywany w poznańskim Archiwum Państwowym.

Following the presentation of the organizational structure and the rules governing the performance of the local branch of the Central Office for Control of the Press, Publications and Entertainment in Poznań, the author focuses on the role of the office in the process of nationalization of private and cooperative printing and publishing sector in Poznań. The article proves that through the very existence of the preventive censorship imposed by the communists of the Stalin era, the communist authorities were in position to accelerate nationalization of the publishing sector. The source materia for the article is provided by available vast and extensive records and files made at the Office for Control in Poznań currently held in the State Archives in Poznań.
The Provincial Office for Control of the Press, Publications and Entertainment at the time of
Keywords: Historia PRL; History of Communist Poland; Historia książki; History of the book; Ruch wydawniczy w Poznaniu; Publishing system in Poznan; Cenzura prewencyjna; Preventive censorship